Molecular dynamics simulations of ch4 clathrate hydrate dissociation adjacent to hydrated silica surfaces - Bagherzadeh, A.; Englezos, Peter; Alavi, S.; Kumar, Rajnish; Ripmeester, John A. (7th International Conference on Gas Hydrates, 2011)
We use molecular dynamics simulations to study the decomposition of structure I CH4 clathrate hydrate exposed to water. Simulations are performed for a hydrate + water system and two related cases with the hydrate adjacent to hydrate silica layers. The simulations are in the NVE adiabatic ensemble paying careful attention to the non-isothermal nature of the hydrate dissociation process. The effects of mass and energy transfer on the hydrate dissociation rate are studied. The effect of the silica surface on the dissociation rate and mechanism are studied. It is observed that the hydrate layer decomposes more quickly in simulations where it is in contact with silica. The implications on decomposition of the hydrate in hydrate reservoirs adjacent to sand sediments are discussed.

Ammonia clathrate hydrates as new solid phases for Titan, Enceladus, and other planetary systems - Shin, Kyuchul; Kumar, Rajnish; Udachin, Konstantin A.; Alavi, Saman; Ripmeester, John A. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
There is interest in the role of ammonia on Saturn's moons Titan and Enceladus as the presence of water, methane, and ammonia under temperature and pressure conditions of the surface and interior make these moons rich environments for the study of phases formed by these materials. Ammonia is known to form solid hemi-, mono-, and dihydrate crystal phases under conditions consistent with the surface of Titan and Enceladus, but has also been assigned a role as water-ice antifreeze and methane hydrate inhibitor which is thought to contribute to the outgassing of methane clathrate hydrates into these moons' atmospheres. Here we show, through direct synthesis from solution and vapor deposition experiments under conditions consistent with extraterrestrial planetary atmospheres, that ammonia forms clathrate hydrates and participates synergistically in clathrate hydrate formation in the presence of methane gas at low temperatures. The binary structure II tetrahydrofuran + ammonia, structure I ammonia, and binary structure I ammonia + methane clathrate hydrate phases synthesized have been characterized by X-ray diffraction, molecular dynamics simulation, and Raman spectroscopy methods.
Keywords: ethane; hydrate inhibitors; hydrogen bonding; ice; single crystal X-ray diffraction

Carbon dioxide capture using amine functionalized silica gel - Sakpal, Tushar; Kumar, Asheesh; Kamble, Sanjay; Kumar, Rajnish (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Commercially available silica gel is chemically modified for carbon dioxide capture. Calcinated silica gel of certain particle size functionalized with amine using two different methods, wet impregnation and grafting via silane chemistry has been employed as a porous media. The prepared material is characterized by Fourier transform infrared, scanning electron microscopy, energy dispersive analysis of X-rays, thermogravimetry and N-2 physisorption techniques. Gas uptake measurements have been carried out to ascertain the CO2 capture capacity of the amine functionalized material. The experiments have been carried out at moderate pressure and temperature range to ascertain its potential for easy scale up.
Keywords: Amine functionalized silica gel; Carbon dioxide capture; grafting; Poly(ethyleneimine); Silane chemistry; Wet impregnation

Multiple H2 occupancy of cages of clathrate hydrate under mild condition - Lu, Hailong; Wang, Jianwei; Liu, Changling; Ratcliffe, Christopher I.; Becker, Udo; Kumar, Rajnish; Ripmeester, John A. (Journal of the American Chemical Society, 2012)
Experiments were carried out by reacting H(2) gas with N(2) hydrate at a temperature of 243 K and a pressure of 15 MPa. The characterizations of the reaction products indicated that multiple H(2) molecules can be loaded into both large and small cages of structure II clathrate hydrates. The realization of multiple H(2) occupancy of hydrate cages under moderate conditions not only brings new insights into hydrogen clathrates but also refreshes the perspective of clathrate hydrates as hydrogen storage media.

HBGS (hydrate based gas separation) process for carbon dioxide capture employing an unstirred reactor with cyclopentane - Ho, Leong Chuan; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
The effect of CP (cyclopentane) as a promoter/additive, in the HBGS (hydrate based gas separation) process for pre-combustion gas mixture was investigated by employing an unstirred reactor configuration. Gas uptake measurements were performed at two different temperatures (275.7 K and 285.7 K) and at an experimental pressure of 6.0 MPa to determine the kinetics of hydrate formation. Experiments were conducted with three different volumes (7.5, 15 and 22 ml) of CP and based on induction time and the rate of hydrate growth, 15 ml of CP was determined to be the optimal volume for carbon dioxide capture at 6.0 MPa and 275.7 K. In addition, the effect of a kinetic promoter, SDS (sodium dodecyl sulfate), was investigated. Surprisingly, no improvement in kinetic performance was observed at 6.0 MPa and 275.7 K in the presence of SDS and CP. From the study, it was found that at the optimal 15 ml CP (CP layer thickness of 1.8 mm), the average composition of carbon dioxide in the hydrate phase was 90.36 mol% with a separation factor of 17.82. Furthermore, the unstirred reactor also yielded better kinetic performance over the stirred tank reactor with the unstirred reactor having a 2.28 times higher average gas uptake. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Cyclopentane; Gas hydrates; Gas separation; Pre-combustion; Unstirred reactor

Heat transfer calculations for decomposition of structure i methane hydrates by molecular dynamics simulation - Baghel, Vikesh Singh; Kumar, Rajnish; Roy, Sudip (Journal of Physical Chemistry C, 2013)
Microcanonical ensemble molecular dynamics simulations of structure I methane hydrate is presented in this work to study the endothermic decomposition process. The mechanism of decomposition of methane hydrate as a function of time was explained at the molecular level. The initial temperature and pressure of the simulation were chosen so as to depict the natural gas hydrate in conditions of oceanic sediments. A more realistic strategy was developed to perform the microcanonical ensemble simulation of solid liquid interface of hydrate and amorphous water. Two water models, SPC/E and TIP4P, were used for the simulations, and the results of the simulations were compared. Heat transfer calculations were performed on the adiabatic system, and an attempt has been made to fit the MD simulation results to the heat balance equations derived from the heat transfer calculations. Estimates of the properties at the macroscopic scale, like the equilibrium temperature of methane hydrate and rate of supply of hot water for sustained release of methane from solid hydrate phase, were determined. The equilibrium temperature obtained by the above method was found to be in agreement with the experimentally observed value. Both the SPC/E and TIP4P water models gave similar results.

Hydrate phase equilibrium of ternary gas mixtures containing carbon dioxide, hydrogen and propane - Babu, Ponnivalavan; Yang, Ting; Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Journal of Chemical Thermodynamics, 2013)
Hydrate phase equilibrium of the ternary guest mixtures containing carbon dioxide, hydrogen and propane at two different compositions were determined. Addition of mole composition of 2.5% propane to the fuel gas (CO2 (40%)/H-2 (60%)) mixture reduces the hydrate formation conditions by 66% at the temperature of 278.4 K. A Clausius-Clapeyron plot for the experimental results was plotted and from the slope, the enthalpy of hydrate dissociation was calculated. The enthalpy of dissociation of the mixed hydrate formed from a ternary gas mixture containing mole composition 38.1% CO2, 59.4% H-2 and 2.5% C3H8 was found to be 110 kJ.mol(-1) and hence it was concluded that the mixed hydrate formed structure II (sII) hydrates. Whereas for the ternary gas mixture containing mole composition 80.0% CO2, 18.8% H-2, and 1.2% C3H8, the enthalpy of dissociation of the mixed hydrate was found to be 78 kJ.mol(-1) and hence we believe the mixed hydrate formed structure I (sI) hydrate. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Phase equilibrium; Pre-combustion; Thermodynamics

Influence of contact medium and surfactants on carbon dioxide clathrate hydrate kinetics - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Fuel, 2013)
Carbon dioxide (CO2) hydrate formation kinetic was investigated in a fixed bed crystallizer at constant pressure (3.55 MPa) and temperature (274 K). Porous media of three different silica gels were used, with a mesh size of 60-120, 100-200 and 230-400 having different surface area. The observed trends indicate that silica gel with larger surface area leads to higher gas consumption as well as reduces the induction time. The effect of pore diameter and particle size distribution has already been reported in a previous study [1]. In this study the effect of additives on hydrate formation kinetics were also investigated. The additives studied were nonionic surfactant Tween-80 (T-80), cationic dodecyltrimethylammonium chloride (DTACl) and anionic Sodium Dodecyl Sulphate (SDS). Out of the three surfactants used in this study, SDS was found to be most effective in enhancing the rate of hydrate formation as well as reducing the induction time. The current result shows significant improvement in water to hydrate conversion in silica gel media compared to quiescent water or surfactant-water system under similar conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrate; kinetics; Silica gel; Surfactants

Low-pressure synthesis and characterization of hydrogen-filled ice ic - Kumar, Rajnish; Klug, Dennis D.; Ratcliffe, Christopher I.; Tulk, Christopher A.; Ripmeester, John A. (Angewandte Chemie-International Edition, 2013)
Keywords: Clathrates; cubic ice; hydrates; Hydrogen

Medium pressure hydrate based gas separation (HBGS) process for pre-combustion capture of carbon dioxide employing a novel fixed bed reactor - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (International Journal of Greenhouse Gas Control, 2013)
This work presents an effective medium pressure hydrate based gas separation (HBGS) process for pre-combustion carbon dioxide capture in a novel fixed bed column. 2.5 mol% propane was added to the fuel gas mixture as an additive to decrease the operating pressure of the HBGS process. Hydrate formation kinetics was investigated at three different pressures (4.5, 5.5 and 6.0 MPa respectively) and at 274.15 K. The performance of silica sand and silica gel as a medium was evaluated. In silica sand bed, multiple nucleation events were observed. In silica gel bed, the gas uptake and water conversion to hydrates was significantly low at any given driving force than that obtained in silica sand bed. Experiments at different water saturation levels (50, 75 and 100%) in silica sand bed were investigated at 6.0 MPa and 274.15 K. It was found that at 50% water saturation, gas consumed for hydrate formation and water conversion to hydrates was almost three times that at 100% saturation. Water to hydrate conversions of up to 64.3% was achieved after 4 h of hydrate formation for the 50% water saturated silica sand bed. Our study presents an opportunity to scale up the HBGS process for CO2 capture with enhanced kinetics by employing a fixed bed reactor configuration. Decomposition experiments at a driving force of Delta T of 10 K and 23K were carried out to recover the gas consumed for hydrate formation and it was found that Delta T of 23 K was sufficient to recover the hydrated gas. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Pre-combustion; Separation

Morphology of carbon dioxide-hydrogen-cyclopentane hydrates with or without sodium dodecyl sulfate - Lim, Yu-An; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Crystal Growth & Design, 2013)
In this study, effects of cyclopentane (CP) and sodium dodecyl sulfate (SDS) on the hydrate formation morphology were investigated. A gas mixture of 40.0 mol % carbon dioxide and 60.0 mol % hydrogen was used in an unstirred system with subcooling as the driving force. Experimental pressure is at 6.0 MPa and experimental temperatures used are at 275.65 and 277.65 K (Delta T = 15.15 and 13.15 K). Formation of hydrates started at the cyclopentane-liquid water interface. Cloud-like, equiaxed skewed dendritic, equiaxed orthogonal dendritic, long dendritic, and cactus-like crystals could be observed for the experiments in the absence of surfactants. Rapid hydrate formation was observed for the experiments with 0.9 mL CP with or without the presence of surfactants compared to the experiments with 0.45 mL CP system at the same experimental conditions. The addition of SDS had led to a change in the hydrate crystal morphology, forming fiber-like crystals from the hydrate layer. Hydrates had also shown affinity to metal surfaces and tend to grow rapidly because of better heat transfer capacity. Gas uptake measurements were found to correlate well with the morphological observations. On the basis of the morphological observations, the mechanism of the CO2-H-2-CP system in an unstirred system is presented.

New porous material to enhance the kinetics of clathrate process: application to precombustion carbon dioxide capture - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Environmental Science & Technology, 2013)
In this work, the performance of a new porous medium, polyurethane (PU) foam in a fixed bed reactor for carbon dioxide separation from fuel gas mixture using the hydrate based gas separation process is evaluated. The kinetics of hydrate formation in the presence of 2.5 mol % propane as thermodynamic promoter was investigated at 4.5, 5.5, and 6.0 MPa and 274.2 K. Significantly higher gas consumption and water conversion to hydrate was achieved when PU foam was employed. PU foam as a porous medium can help convert 54% of water to hydrate in two hours of hydrate formation. In addition the induction times were very low (<3.67 min at 6.0 MPa). A normalized rate of hydrate formation of 64.48 (+/- 3.82) mol.min(-1).m(-3) was obtained at 6.0 MPa and 274.2 K. Based on a morphological study, the mechanism of hydrate formation from water dispersed in interstitial pore space of the porous medium is presented. Finally, we propose a four step operation of the hydrate based gas separation process to scale up.

Pre-combustion capture of carbon dioxide in a fixed bed reactor using the clathrate hydrate process - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
Hydrate based gas separation (HBGS) process with silica sand and silica gel as contact medium was employed to capture CO2 from fuel gas mixture. Gas uptake measurement at three different pressures (7.5, 8.5 and 9.0 MPa) and 274.15 K were conducted for hydrate formation kinetics and overall conversion of water to hydrate, rate of hydrate formation were determined. Water conversion of up to 36% was achieved with silica sand bed compared to 13% conversion in the silica gel bed. Effect of driving force on the rate of hydrate formation and gas consumption was significant in silica sand bed whereas it was found to be insignificant in silica gel bed. Hydrate dissociation experiments by thermal stimulation (at constant pressure) alone and a combination of depressurization and thermal stimulation were carried out for complete recovery of the hydrated gas. A driving force of 23 K was found to be sufficient to recover all the hydrated gas within 1 h. This study indicates that silica sand can be an effective porous media for separation of CO2 from fuel gas when compared to silica gel. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrates; Gas separation; Global warming; Pre-combustion

Enhanced kinetics for the clathrate process in a fixed bed reactor in the presence of liquid promoters for pre-combustion carbon dioxide capture - Babu, Ponnivalavan; Ho, Chie Yin; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
In this work, we present enhanced kinetics of hydrate formation for the clathrate process in the presence of two liquid promoters namely THF (tetrahydrofuran) and TBAB (tetra-n-butyl ammonium bromide) in a FBR (fixed bed reactor) for pre-combustion capture of CO2. Silica sand was used as a medium to capture CO2 from CO2/H-2 gas mixture by hydrate crystallisation. Experiments were performed at different temperatures (274.2 K and 279.2 K) and 6.0 MPa to determine the total gas uptake, induction time and rate of hydrate formation. The observed trends indicated that higher driving force resulted in higher gas consumption and significantly reduced induction time. For the same driving force, higher gas consumption and shorter induction time was achieved by THF as compared to TBAB. 5.53 mol% THF attained higher gas consumption than 1.0 mol% THF whereas 3.0 mol% TBAB attained lower gas consumption than 0.3 mol% TBAB. A highest gas uptake of 51.95 (+/- 5.183) mmol of gas/mol of water and a highest rate of 51.21(+/- 8.91) mol.min(-1).m(-3) were obtained for 5.53 mol% THF at 6.0 MPa and 279.2 K. Overall, this study indicated better hydrate formation kinetics with the use of THF in an FBR configuration for CO2 capture from a fuel gas mixture. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Fixed bed reactor; Gas hydrates; Pre-combustion capture; Promoters

Hydrogen storage in clathrate hydrates: Current state of the art and future directions - Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Applied Energy, 2014)
Hydrogen is looked upon as the next generation clean energy carrier, search for an efficient material and method for storing hydrogen has been pursued relentlessly. Improving hydrogen storage capacity to meet DOE targets has been challenging and research efforts are continuously put forth to achieve the set targets and to make hydrogen storage a commercially realizable process. This review comprehensively summarizes the state of the art experimental work conducted on the storage of hydrogen as hydrogen clathrates both at the molecular level and macroscopic level. It identifies future directions and challenges for this exciting area of research. Hydrogen storage capacities of different clathrate structures - sI, sII, sH, sVI and semi clathrates have been compiled and presented. In addition, promising new approaches for increasing hydrogen storage capacity have been described. Future directions for achieving increased hydrogen storage and process scale up have been outlined. Despite few limitations in storing hydrogen in the form of clathrates, this domain receives prominent attention due to more environmental-friendly method of synthesis, easy recovery of molecular hydrogen with minimum energy requirement, and improved safety of the process. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Clathrates; Gas hydrates; Hydrogen hydrates; Hydrogen storage; Promoters; Storage capacity

Impact of experimental pressure and temperature on semiclathrate hydrate formation for pre-combustion capture of CO2 using tetra-n-butyl ammonium nitrate - Babu, Ponnivalavan; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
TBANO(3) (tetra-n-butyl ammonium nitrate) is a promising liquid phase promoter for capturing CO2 via HBGS (hydrate based gas separation) technology. In this study, the impact of experimental pressure and temperature on formation of mixed CO2-H-2-TBANO(3) semiclathrate hydrate for the optimum 1.0 mol% TBANO(3) reported by Babu et al. [1] was investigated. Experimental pressures of 3.0, 4.5 and 6.0 MPa and temperatures of 274.2, 276.2 and 278.2 K were employed. Irrespective of the experimental pressure, shorter induction time was observed for experiments conducted at 274.2 K when compared to the experiments at other temperatures. At a given pressure, the total gas uptake increased with increase in experimental temperature. Similarly at a given temperature, the total gas uptake increases with an increase in pressure. Higher rate of hydrate formation was observed at experimental pressure of 6.0 MPa than at 3.0 and 4.5 MPa irrespective of the experimental temperature. The CO2 composition in hydrate was between 87.5 and 93.2 mol%. Finally, the gas consumption for 1.0 mol% TBANO(3) as promoter was much higher than other promoters of quaternary salts like tetra-n-butyl ammonium bromide and tetra-n-butyl ammonium fluoride at comparable concentration and driving force. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Semi-clathrates

Impact of fly ash impurity on the hydrate-based gas separation process for carbon dioxide capture from a flue gas mixture - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2014)
The hydrate-based gas separation (HBGS) process for gas mixtures of CO2 + N-2 (flue gas) and CO2 + H-2 (fuel gas) has proven to be very efficient and highly selective for CO2 capture. In addition to CO2 and N-2, flue gas from coal-based thermal power stations can contain impurities such as nitrogen oxides (NOx), sulfur oxides (SOx), and fly ash. In this work, the impact of fly ash on the HBGS process efficiency was investigated. Tetrahydrofuran (THF, 1 mol %) was used as a thermodynamic promoter, and sodium dodecyl sulfate (SDS) and sodium dodecyl benzenesulfonate (SDBS) (anionic surfactants) were used as kinetic promoters. Whereas the use of THF in the HBGS process reduces the operating pressure significantly, both SDS and SDBS were found to enhance the rate of hydrate formation. It was observed that the hydrate equilibrium conditions did not change in the presence of fly ash. However, the presence of fly ash enhanced the separation efficiency of the HBGS process by reducing the induction time and increasing the kinetics of hydrate formation. Therefore, the presence of fly ash in a flue gas mixture is not detrimental to the HBGS process, which is a positive factor for the capture and geological sequestration of CO2 in the form of gas hydrates.

Impact of pressure and temperature on tetra-n-butyl ammonium bromide semi-clathrate process for carbon dioxide capture - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (International Conference on Applied Energy, ICAE2014, 2014)
The pre-combustion capture of CO2 in an IGCC power plant employing the hydrate based gas separation (HBGS) process is a novel method currently receiving attention around the world. Tetra-n-butyl ammonium bromide (TBAB) is a promoter that has been shown to improve the efficiency of hydrate formation. In this study, the effect of temperature and pressure on 0.3 mol% TBAB solution is investigated. The induction time for the experiments conducted at 6.0 MPa and 274.8 K was found to be lower, while nucleation became increasingly random as temperature is increased and pressure is reduced. Total gas uptake and normalized rate of hydrate formation (NR5) is also the highest for the experiments conducted at 6.0 MPa and 274.8 K. However, it was found that the hydrate phase CO2 composition remains relatively constant at both reduced temperatures and pressures. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; Promoters; tetra-n-butyl ammonium bromide

Systematic evaluation of tetra-n-butyl ammonium bromide (TBAB) for carbon dioxide capture employing the clathrate process - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (Industrial & Engineering Chemistry Research, 2014)
Hydrate based gas separation (HBGS) process for the precombustion capture of CO2 from a fuel gas mixture is a novel method being investigated among the carbon capture and sequestration techniques to reduce CO2 emissions. The efficiency of the HGBS process can be improved by using promoters that reduce the formation pressure of mixed gas hydrates. In this study the effect of tetra-n-butyl ammonium bromide (TBAB) was systematically investigated at a constant temperature of 279.2 K and pressure of 6.0 MPa for different TBAB concentrations of 0.3, 1.0, 1.5, 2.0, and 3.0 mol %, respectively. The 0.3 mol % solutions had a relatively longer average induction time of 20.1 min but exhibited the highest total normalized gas uptake of 0.0104 (+/- 0.0004) mol of gas/mol of water and highest separation factor of 41.51 (+/- 6.391). On the other hand, the 1.0 mol % solution had very short average induction time (<0.5 min) and it had the highest hydrate growth rate of 60.8 (+/- 9.89) mol of gas. min(-1).m(-3), with the separation factor of 13.78 (+/- 3.30). Gas solubility measurements and microscopic images of the hydrate formation were also presented to provide greater insights into the effect of TBAB concentration on the gas uptake.

Thermodynamic and kinetic verification of tetra-n-butyl ammonium nitrate (TBANO(3)) as a promoter for the clathrate process applicable to precombustion carbon dioxide capture - Babu, Ponnivalavan; Yao, Minghuang; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Environmental Science & Technology, 2014)
In this study, tetra-n-butyl ammonium nitrate (TBANO(3)) is evaluated as a promoter for precombustion capture of CO2 via hydrate formation. New hydrate phase equilibrium data for fuel gas (CO2/H-2) mixture in presence of TBANO(3) of various concentrations of 0.5, 1.0, 2.0, 3.0, and 3.7 mol % was determined and presented. Heat of hydrate dissociation was calculated using Clausius-Clapeyron equation and as the concentration of TBANO(3) increases, the heat of hydrate dissociation also increases. Kinetic performance of TBANO(3) as a promoter at different concentrations was evaluated at 6.0 MPa and 274.2 K. Based on induction time, gas uptake, separation factor, hydrate phase CO2 composition, and rate of hydrate growth, 1.0 mol % TBANO(3) solution was found to be the optimum concentration at the experimental conditions of 6.0 MPa and 274.2 K for gas hydrate formation. A 93.0 mol % CO2 rich stream can be produced with a gas uptake of 0.0132 mol of gas/mol of water after one stage of hydrate formation in the presence of 1.0 mol % TBANO(3) solution. Solubility measurements and microscopic images of kinetic measurements provide further insights to understand the reason for 1.0 mol % TBANO(3) to be the optimum concentration.

Unusual behavior of propane as a co-guest during hydrate formation in silica sand: potential application to seawater desalination and carbon dioxide capture - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Chemical Engineering Science, 2014)
We report an unusual behavior of hydrate formation in silica sand with gas mixtures containing propane as a co-guest. Based on morphology study we observed that propane as a co-guest has the ability to draw water dispersed in silica sand to the hydrate formation region and showed a tendency to result in drastic hydrate growth due to the migration of water molecules to the gas phase region. Hydrate nucleation occurred in the interstitial pore space between the silica sand particles and hydrate growth occurred in the gas phase above the silica sand bed and to sustain the hydrate growth, dispersed water was drawn towards the hydrate growth front. In addition, we elucidated the effect of sand bed height to maximize the growth rates utilizing this behavior that results in enhanced kinetics. We propose conceptual designs for utilizing this behavior of propane as a co-guest in sand for seawater desalination and an innovative approach to simultaneously capture carbon dioxide and desalinate seawater. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Desalination; Enhanced kinetics; Gas hydrates; Propane hydrate: pre-combusuon capture

Carbon dioxide sequestration: influence of porous media on hydrate formation kinetics - Bhattacharjee, Gaurav; Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (ACS Sustainable Chemistry & Engineering, 2015)
In the present study, CO, sequestration by hydrate formation in porous sediments has been discussed. Two siliceous materials with high porosities, pumice and fire hardened red clay (FHRC), have been used as packing materials in a fixed bed setup to study hydrate formation kinetics. The results obtained using the aforementioned materials were compared with those obtained using silica sand and quartz. Carbon dioxide hydrate formation kinetics was studied at 3.0 MPa pressure and 274 K temperature. Two different types of experiments were conducted: (a) using a constant volume of water and (b) maintaining a constant bed height. These experiments were conducted using the different porous media individually as packing materials. It was observed that pumice as the porous medium showed better hydrate formation kinetics resulting in 46 mol % water to hydrate conversion in 5 h. Moreover, kinetics was enhanced with decrease in the bed height of pumice; this suggests that at field scale adaptation of CO, sequestration in geological formations, mass transfer limitations would be significant. The effects of particle size on hydrate formation kinetics were also investigated. It was observed that hydrate formation kinetics was enhanced with decrease in the particle size fraction.
Keywords: Bed height; Gas hydrate; gas uptake; Geological sequestration; Particle size

Enhanced carbon dioxide hydrate formation kinetics in a fixed bed reactor filled with metallic packing - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Chemical Engineering Science, 2015)

Influence of low-dosage hydrate inhibitors on methane clathrate hydrate formation and dissociation kinetics - Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (Energy Technology, 2015)
This work investigates the effect of low-dosage hydrate inhibitors (LDHIs) on methane hydrate formation and dissociation. The hydrate inhibitors used in this study were the sodium salt of polyacrylic acid, a polysaccharide chitosan, and the linear sulfated polysaccharide i-carrageenan; the inhibiting behavior of these additives were compared with that of the commonly used hydrate inhibitor polyvinylpyrrolidone for methane hydrate formation. A LDHI concentration of 1wt% was found to increase the induction time relative to that at a LDHI concentration of 0.1wt%. Chitosan was found to be better than the others in reducing nucleation and the growth rate of the hydrate at a concentration of 1wt%. At a lower concentration of 0.1wt%, nucleation inhibition was minimal, however, growth inhibition was significant. The effect of these inhibitors on the decomposition rate of the hydrate was also studied, and the decomposition kinetics at a constant driving force in excess of three-phase equilibrium is reported.
Keywords: gas uptake; hydrates; inhibitors; kinetics; thermal stimulation

Methane hydrate formation in a test sediment of sand and clay at various levels of water saturation - Kumar, Asheesh; Sakpal, Tushar; Roy, Sudip; Kumar, Rajnish (Canadian Journal of Chemistry, 2015)
Kinetics of methane hydrate formation with different ratios of silica sand and clay and different water saturations were studied. At suitable temperature and methane gas pressure, water in the void spaces of silica sand packing and intercalated area of clay were converted into hydrate. It was observed that the rate of hydrate formation increases with higher void space in the packing, and addition of clay in test sediment decreases water to hydrate conversion as well as rate of hydrate formation. Maximum water to hydrate conversion of 60.0% was achieved in pure silica sand bed at 75% water saturation. Presence of fine clay particles is expected to reduce the void spaces and thus may hinder effective mass transfer of hydrate forming gases in the bed. However, it is also possible that the bentonite clay used in this work may actually inhibit hydrate growth. Additional experiments in stirred tank reactor were carried out to understand the inhibiting effect of bentonite clay for hydrate formation.
Keywords: clay; formation kinetics; methane hydrate; Silica sand; water saturation

Molecular dynamics study of model SI clathrate hydrates: the effect of guest size and guest-water interaction on decomposition kinetics - Das, Subhadip; Baghel, Vikesh Singh; Roy, Sudip; Kumar, Rajnish (Physical Chemistry Chemical Physics, 2015)
One of the options suggested for methane recovery from natural gas hydrates is molecular replacement of methane by suitable guests like CO2 and N-2. This approach has been found to be feasible through many experimental and molecular dynamics simulation studies. However, the long term stability of the resultant hydrate needs to be evaluated; the decomposition rate of these hydrates is expected to depend on the interaction between these guest and water molecules. In this work, molecular dynamics simulation has been performed to illustrate the effect of guest molecules with different sizes and interaction strengths with water on structure I (SI) hydrate decomposition and hence the stability. The van der Waals interaction between water of hydrate cages and guest molecules is defined by Lennard Jones potential parameters. A wide range of parameter spaces has been scanned by changing the guest molecules in the SI hydrate, which acts as a model gas for occupying the small and large cages of the SI hydrate. All atomistic simulation results show that the stability of the hydrate is sensitive to the size and interaction of the guest molecules with hydrate water. The increase in the interaction of guest molecules with water stabilizes the hydrate, which in turn shows a slower rate of hydrate decomposition. Similarly guest molecules with a reasonably small (similar to Helium) or large size increase the decomposition rate. The results were also analyzed by calculating the structural order parameter to understand the dynamics of crystal structure and correlated with the release rate of guest molecules from the solid hydrate phase. The results have been explained based on the calculation of potential energies felt by guest molecules in amorphous water, hydrate bulk and hydrate-water interface regions.

Review of the hydrate based gas separation (HBGS) process for carbon dioxide pre-combustion capture - Babu, Ponnivalavan; Linga, Praveen; Kumar, Rajnish; Englezos, Peter (Energy, 2015)
In this work, a systematic review of the literature work done so far on the use of hydrate crystallization as a basis to develop data for the hydrate based gas separation (HBGS) process for the capture of CO2 from fuel gas mixtures is presented. Such a gas mixture may arise in integrated gasification combined cycle (IGCC) power plants. A thorough assessment of the thermodynamic, kinetic factors and economic aspects of the HBGS process and critical comments are presented. Compared with competing technologies, high CO2 capacity and the use of water as a solvent are key advantages for the HBGS process for CO2 capture. Furthermore, in this review, a snapshot of the current state-of-the-art is presented and further research and development opportunities and pathways for commercializing the HBGS process for pre-combustion capture of CO2 from IGCC power plants are discussed. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; IGCC plants; Pre-combustion capture

Role of metallic packing and kinetic promoter in designing a hydrate-based gas separation process - Kumar, Asheesh; Kumar, Rajnish (Energy & Fuels, 2015)
In the present work, kinetics of the hydrate-based gas separation (HBGS) process has been studied employing an unstirred reactor configuration. Gas uptake measurements were carried out for studying hydrate formation kinetics and final water to hydrate conversion using fuel gas mixtures (mixture 1, 40.4% CO2 + 59.6% H-2; mixture 2, 40.9% CO2 + 58.05% H-2 + 1.05% H2S). Silica sand and stainless-steel-structured packing (SSP) were used as contact media in the presence of an anionic surfactant sodium dodecyl sulfate (SDS) as a kinetic promoter. Experiments were conducted with three different concentrations of SDS in water to enhance hydrate formation kinetics. On the basis of induction time and rate of hydrate growth, 1 wt % SDS was determined to be the best concentration for carbon dioxide capture at 7.0 MPa and 273.65 K from the CO2 + H-2 gas mixture. In comparison to silica sand packing, use of SSP was found to improve the final water to hydrate conversion (71.0 +/- 4.1%). The addition of H2S impurity in the fuel gas mixture was also found to enhance the rate of hydrate formation in the presence of SDS at 7.8 MPa and 274.5 K. On the basis of the experimental results and our previous studies on separation efficiency, a continuous HBGS process is proposed to separate CO2 and produce CO2- and H2S-free H-2 stream from a fuel gas mixture.

Role of surfactants in promoting gas hydrate formation - Kumar, Asheesh; Bhattacharjee, Gaurav; Kulkarni, B. D.; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2015)
Gas hydrates have been proposed as a potential technology for a number of applications, such as separation of gas mixtures, CO2 capture, transportation, and sequestration, methane storage and transport, and seawater desalination. Most of these applications will benefit from reduced induction time of hydrate nucleation, enhanced hydrate growth rate, and maximum water-to-hydrate conversion. The addition of surfactants to the gas-water system serves this purpose in a very effective manner. This review focuses on different surfactants that were utilized for gas hydrate formation studies; insights have been provided on the possible mechanisms of action through which these surfactants affect hydrate formation kinetics. A thorough analysis of the existing literature on surfactants suggests that enhanced rate of hydrate nucleation and growth kinetics may not be directly linked to micelle formation. Conversely, reduced surface tension in the presence of surfactants not only enhances the mass transfer but also changes the morphology of hydrate formation, which in turn enhances gas-water interactions for faster hydrate growth rate.

Biosurfactant as a promoter of methane hydrate formation: thermodynamic and kinetic studies - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Balomajumder, Chandrajit; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Scientific Reports, 2016)
Natural gas hydrates (NGHs) are solid non-stoichiometric compounds often regarded as a next generation energy source. Successful commercialization of NGH is curtailed by lack of efficient and safe technology for generation, dissociation, storage and transportation. The present work studied the influence of environment compatible biosurfactant on gas hydrate formation. Biosurfactant was produced by Pseudomonas aeruginosa strain A11 and was characterized as rhamnolipids. Purified rhamnolipids reduced the surface tension of water from 72 mN/m to 36 mN/m with Critical Micelle Concentration (CMC) of 70 mg/l. Use of 1000 ppm rhamnolipids solution in C type silica gel bed system increased methane hydrate formation rate by 42.97% and reduced the induction time of hydrate formation by 22.63% as compared to water saturated C type silica gel. Presence of rhamnolipids also shifted methane hydrate formation temperature to higher values relative to the system without biosurfactant. Results from thermodynamic and kinetic studies suggest that rhamnolipids can be applied as environment friendly methane hydrate promoter.

Crystallization kinetics for carbon dioxide gas hydrate in fixed bed and stirred tank reactor - Kumar, Asheesh; Khatri, Dishant; Lee, Ju Dong; Kumar, Rajnish (Korean Journal of Chemical Engineering, 2016)
The phase change from germ nuclei to growth nuclei and subsequent volume transformation in a crystallization process was modeled by Avrami equations. The phase change during the hydrate formation was fitted with the classical Avrami model by utilizing gas uptake data. The idea is to understand the difference in growth behavior of hydrate crystals when in small pores compared to a stirred tank reactor which does not pose any physical restrictions to hydrate growth. The parameters n and k of the Avrami equation were determined explicitly for CO2 hydrate formation.
Keywords: Avrami Equation; CO2 Capture & Sequestration; Fixed Bed; Gas hydrates; kinetics

Effect of additives on formation and decomposition kinetics of methane clathrate hydrates: application in energy storage and transportation - Kumar, Asheesh; Kushwaha, Omkar Singh; Rangsunvigit, Pramoch; Linga, Praveen; Kumar, Rajnish (Canadian Journal of Chemical Engineering, 2016)
Methane gas storage and transportation via clathrate hydrates is proposed to be a potential solution for large-scale energy storage. In this work, we study the formation and decomposition kinetics of methane hydrates (MH) in a laboratory-scale unstirred crystallizer. The present investigation demonstrates comparative studies of hydrate formation and dissociation kinetics in the presence of tetrahydrofuran (55.6 and 27.8mmol/mol, 5.56 and 2.78mol% THF) and sodium dodecyl sulphate (1mg/g, 0.1wt% SDS). Moreover, the storage capacity and hydrate formation kinetics in both the systems are discussed. In a recent work, enhanced methane hydrate growth in the presence of THF at close to atmospheric conditions was demonstrated. The emphasis of the current work is to study the stability of hydrates to understand dissociation kinetics by measuring the rate of hydrate decomposition at different temperatures. Hydrate stability measurements were performed at -8, -3, 2, 10, and 20 degrees C to study the decomposition rates of MH and self-preservation in presence of the two additives THF and SDS.

Effect of polyvinylpyrrolidone at methane hydrate-liquid water interface. application in flow assurance and natural gas hydrate exploitation - Choudhary, Nilesh; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Fuel, 2016)

Effect of the amino acid L-histidine on methane hydrate growth kinetics - Bhattacharjee, Gaurav; Choudhary, Nilesh; Kumar, Asheesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Natural Gas Science and Engineering, 2016)
In the present study, the effect of a polar amino acid, L-histidine on methane hydrate growth kinetics has been investigated. Methane hydrate formation experiments were carried out in a stirred tank reactor setup at pressure and temperature conditions of 274.15 K and 5.0 MPa respectively. Two different concentrations (0.1 and 1 wt %) of L-histidine were studied. Hydrate growth through molecular dynamic (MD) simulation was also studied; pressure and temperature conditions for the simulations were set at 10.0 MPa and 270.0 K, while the concentration of L-histidine was kept fixed at 0.94 wt %. Hydrate formation runs using MD simulation were carried out with optimal concentration of methane in water. The presence of L-histidine in the system was found to significantly enhance methane hydrate growth kinetics as compared to pure water for both experimental and MD simulation runs. Final gas consumption with 1 wt % L-histidine was found to be comparable to that with 1 wt % SDS, the most commonly used additive for hydrate promotion studies. L-histidine is a benign additive which offers considerable enhancement in methane hydrate formation kinetics and can be utilized for various hydrate based technologies such as methane storage and transport. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Crystal growth; Gas hydrate; kinetics; Molecular dynamic simulation

Enhanced clathrate hydrate formation kinetics at near ambient temperatures and moderate pressures: Application to natural gas storage - Veluswamy, Hari Prakash; Kumar, Sharad; Kumar, Rajnish; Rangsunvigit, Pramoch; Linga, Praveen (Fuel, 2016)
SNG (solidified natural gas) technology via clathrate hydrates is a potential method for large scale stationary storage of natural gas. Clathrate hydrate formation kinetics in presence of methane and 5.6 mol% tetrahydrofuran (THF) was investigated in an unstirred reactor configuration at moderate pressure and temperature conditions. It is well known that the presence of THF generally improves the thermodynamic stability of the resulting hydrate. In order to study the scale-up potential of this approach, kinetics of hydrate growth at temperatures close to ambient conditions and moderate pressures is required. Hydrate formation experiments were performed at three different temperatures - 283.2 K, 288.2 K and 293.2 K and at experimental pressures of 7.2 MPa, 5.0 and 3.0 MPa. Further, we report a synergistic effect of kinetic promotion of mixed methane hydrate formation by coupling THF and sodium dodecyl sulfate (SDS) at 293.2 K. For the first time, we observe rapid mixed methane/THF hydrate formation kinetics at 293.2 K in presence of just 100 ppm sodium dodecyl sulfate surfactant with methane gas uptake of 3.45 (+/- 0.17) kmol/m(3) of water in 1 h. This is also the first study to demonstrate such rapid hydrate formation kinetics with significant methane storage capacity at temperature of 293.2 K (closer to the ambient temperature). Further, substantial methane gas uptake of 3.52 (+/- 0.13) kmol/m(3) of water is possible even at reduced experimental pressure of 3.0 MPa and 283.2 K in 2 h. Minimal energy requirement in an unstirred reactor for mixed methane/THF hydrate formation storage can propel the SNG technology for large scale commercial deployment. Further improvement in the process can be achieved by optimizing the cooling requirement through innovative reactor design and operating the process in a semi-batch or continuous mode. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Methane hydrates; Natural gas storage; Rapid kinetics; surfactant; Tetrahydrofuran; Unstirred reactor

Experimental investigation to elucidate why tetrahydrofuran rapidly promotes methane hydrate formation kinetics: applicable to energy storage - Kumar, Asheesh; Daraboina, Nagu; Kumar, Rajnish; Linga, Praveen (Journal of Physical Chemistry C, 2016)
Methane storage as SNG (solidified natural gas) in the form of clathrate hydrates is an emerging, economically feasible and environmentally benign technology for large scale storage. Mixed tetrahydrofuran (THF)-methane (CH4) hydrates offer a paradigm shift to milder storage conditions and faster hydrate formation kinetics, providing a promising scenario to scale up the SNG technology. In this work, we synthesize mixed THF-CH4 hydrates in a high pressure microdifferential scanning calorimeter (HP mu-DSC) to elucidate the two-step hydrate formation mechanism of mixed THF-CH4 hydrate identifying the synergism between THF and CH4. Heat flow change during hydrate formation and dissociation of mixed THF-CH4 hydrates formed in the presence of 5.56 mol % THF (stoichiometric composition) were monitored. The two step-mechanism of mixed THF-CH4 hydrate formation was further confirmed by the pressure-temperature profile and visual observations with a sample volume scale -up of about 350 times that of mu-DSC experiments.

Impact of H2S impurity on carbon dioxide hydrate formation kinetics in fixed bed arrangements - Kumar, Asheesh; Sakpal, Tushar; Bhattacharjee, Gaurav; Kumar, Anupam; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2016)
In the present work, a combination of silica sand and metallic sheets as a fixed bed media was used for carbon dioxide hydrate formation studies. Two metallic sheets, aluminum and brass, were incorporated into the fixed bed of silica sand to enhance heat transfer properties of the bed. The results obtained from this arrangement of metal sheets were compared with those obtained with a pure silica sand system. Both brass and aluminum systems were found to be good candidates to enhance gas hydrate formation kinetics compared to simply a sand system. Production of fuel gas from coal often contains a toxic gas, hydrogen sulfide (H2S). For the first time, the effect of H2S on the formation kinetics of CO2 + H-2 + H2S hydrates has been studied. It was observed that the presence of H2S does not affect the hydrate formation kinetics and total gas uptake in the presence of H2S is either as good as CO2 + H-2 hydrate or better. However, H2S impurity in the fuel gas mixture shows a corrosive effect on silica sand media.

Rapid methane hydrate formation to develop a cost effective large scale energy storage system - Veluswamy, Hari Prakash; Wong, Alison Jia Hui; Babu, Ponnivalavan; Kumar, Rajnish; Kulprathipanja, Santi; Rangsunvigit, Pramoch; Linga, Praveen (Chemical Engineering Journal, 2016)
Natural gas (NG) is the cleanest burning fossil fuel and its usage can significantly reduce CO2 emissions from power plants. With its widespread use, there is an ever increasing need to develop technologies to store NG on a large scale. NG storage via clathrate hydrates is the best option for a large scale storage system because of its non-explosive nature, mild storage conditions, high volumetric capacity and being an environmentally benign process. In this work, we demonstrate a new method to achieve rapid methane hydrate formation in an unstirred tank reactor configuration (UTR) at moderate temperature and pressure conditions employing tetrahydrofuran (THF) as a promoter. For the first time, THF is reported to act both as a thermodynamic and an excellent kinetic promoter for methane hydrate formation. We demonstrate a multi-scale experimental validation of our method to a volumetric sample scale-up factor of 120 and internal reactor diameter scale-up factor of 10. Further, new insights on the dissociation behavior of the hydrates are reported. There is a competitive edge for storing NG via clathrate hydrates compared to compressed natural gas storage both in terms of cost and safety. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Energy storage; Enhanced kinetics; Gas hydrates; Natural gas storage; Tetrahydrofuran; Unstirred tank reactor

Role of Rhamnolipid: A biosurfactant in methane gas hydrate formation kinetics - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Singh, Anil Kumar; Kumar, Pushpendra; Balomajumder, Chandrajit; Laik, Sukumar (Proceedings of The First International Conference on Recent Advances in Bioenergy Research, 2016)
Naturally occurring methane gas hydrate is a vast source of methane gas which is trapped in crystalline ice-like structure present in permafrost regions and under the sea in outer continental margins. It is purposed that total amount of carbon in the form of methane hydrates is almost twice the carbon content in all the fossil fuel reserves put together, and hence these are supposed to be the future potential energy resource. This paper investigates the laboratory investigations on effect of a biosurfactant rhamnolipid on methane hydrate formation kinetics. Rhamnolipid was produced by Pseudomonas aeruginosa strain A11. The presence of P. aeruginosa has been reported in Gulf of Mexico gas hydrate samples. Biosurfactant reduced the surface tension of water from 72 to 36 mN/m with CMC of 70 mg/L. The biosurfactant dose is studied at two different concentrations in the solution at 100 and 1000 ppm. Kinetic of hydrate formation and growth is compared at 0, 100, and 1000 ppm of rhamnolipid showing that rhamnolipid acts as a hydrate promoter at these concentrations. Thus, small dosages of rhamnolipids produced by P. aeruginosa strain A11 must clearly affect the gas hydrate formation kinetics in natural sites (as in Gulf of Mexico).
Keywords: Induction time; methane hydrate; Potential energy resource; Pseudomonas aeruginosa; Rhamnolipid

Biosurfactant surfactin as a kinetic promoter for methane hydrate formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Pradhan, Darshan; Naik, Rajesh; Zare, Kirti; Mawlankar, Rahul R.; Dastager, Syed Gulam; Kushwaha, Omkar Singh; Kumar, Rajnish (Energy Procedia, 2017)
In the present study, the effect of the biosurfactant Surfactin on methane hydrate formation kinetics was studied. Initially, several marine derived species were screened for the presence of Surfactin. The polymerase chain reaction technique was used as the preliminary screening step for Surfactin which was then followed up by a couple of different assays to provide conclusive evidence of the same. Based on these tests, the D-9 bacterial strain was identified as a producer of Surfactin. Once the presence of Surfactin had been proven, its effect on methane hydrate formation kinetics was investigated upon by carrying out hydrate formation experiments in a stirred tank reactor. The cell free supernatant containing Surfactin was itself used as the hydrate forming solution without any further processing. It was found that the presence of Surfactin in the system greatly enhances hydrate formation kinetics as compared to pure water. In fact the kinetics in presence of Surfactin also surpassed that obtained with 1 wt% SDS, the most commonly used synthetic kinetic hydrate promoter. This basic study can pave the way for more sophisticated research on the use of biosurfactants as kinetic promoters with a view on rapid methane hydrate formation kinetics for applications such as methane separation, storage and transport.

Effect of shape of protrusions and roughness on the hydrophilicity of a surface - Chowdhury, Sheelan Sengupta; Pandey, Prithvi Raj; Kumar, Rajnish; Roy, Sudip (Chemical Physics Letters, 2017)
We have investigated wetting of model rough surfaces made up of hydrophilic triangular and hexagonal pillars (protrusions). The surface roughnesses are altered by varying the area of the rough surface, the height of the pillars, and the surface interactions to the water. We have established a correlation between structure i.e., the shape of a pillar, which actually depends on the number of edges (due to shape), and the wetting phenomena. We have found that surface with higher number of edges repels water at lower roughness value. We explain the correlation by analyzing the variation of interactions energy components and density profiles of water on the structured surfaces. (C) 2017 Elsevier B.V. All rights reserved.

Effects of micellization on growth kinetics of methane hydrate - Bhattacharjee, Gaurav; Kushwaha, Omkar Singh; Kumar, Asheesh; Khan, Muzammil Yusuf; Patel, Jay Narayan; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2017)
Surfactants are Specific functional materials, that form various types of self-assemblies and affect local water ordering alongside solution properties. Such surface active agents are used extensively in gas hydrate based applications as kinetic hydrate promoters. To understand the effect of surfactant micelles on hydrate formation kinetics, a novel surfactant system capable of producing micelles at hydrate forming temperature was developed. The presence of surfactant micelles in this new system (a combination of anionic surfactant SDS and zwitterionic surfactant CAPB) was determined through DLS measurements. Pure methane and a coal bed methane mixture were individually used to assess the efficacy of the surfactant mixture for hydrate formation. This study conclusively proves for the first time that the presence of surfactant micelles enhances hydrate formation kinetics. The findings reported here can contribute significantly toward improving the utility of surfactants in gas hydrate based technological applications such as gas separation and methane storage.

Molecular dynamics simulation and experimental study on the growth of methane hydrate in presence of methanol and sodium chloride - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Energy Procedia, 2017)
The plugging of processing and transportation lines by gas hydrate formation is a challenging problem for safe exploitation of oil and gas. The existence of water soluble third component (like methanol and sodium chloride) in the aqueous phase influence the gas hydrate formation thermodynamically also possibly affects the kinetics of hydrate growth. Inorganic salt and organic molecule (alcohols) at high concentration in the aqueous phase have been used as thermodynamic inhibitors to effectively prevent the hydrate formation. This study utilizes molecular dynamics as well as an experimental method to investigate the mechanism of the hydrate formation and the effect of additives. The MD simulation showed that at moderate temperature and pressure, a low concentration (1 wt %) of methanol and NaCl enhances methane hydrate growth kinetics. Significant numbers of methanol molecules were observed inside the gas hydrate cages whereas Na⁺/Cl⁻ ions leach out during hydrate formation.

Effect of sodium dodecyl sulfate surfactant on methane hydrate formation: a molecular dynamics study - Choudhary, Nilesh; Hande, Vrushali R.; Roy, Sudip; Chakrabarty, Suman; Kumar, Rajnish (Journal of Physical Chemistry B, 2018)
In experimental studies, it has been observed that the presence of sodium dodecyl sulfate (SDS) significantly increases the kinetics of hydrate formation and the final water-to-hydrate conversion ratio. In this study, we intend to understand the molecular mechanism behind the effect of SDS on the formation of methane hydrate through molecular dynamics simulation. Hydrate formation conditions similar to that of laboratory experiments were chosen to study hydrate growth kinetics in 1 wt % SDS solution. We also investigate the effect of interactions with isolated SDS molecules on methane hydrate growth. It was observed that the hydrophobic tail part of the SDS molecule favorably interacts with the growing hydrate surface and may occupy the partial hydrate cages while the head groups remain exposed to water.

Kinetic promotion of methane hydrate formation by combining anionic and silicone surfactants: scalability promise of methane storage due to prevention of foam formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Kushwaha, Omkar S.; Kumar, Rajnish (Journal of Chemical Thermodynamics, 2018)
Methane storage in its solid hydrate form has recently come up as a rather attractive and low risk option for large scale storage of the gas owing to its mild storage conditions, high gas retention capacity and benign (non-explosive) character. However, it has its fair share of limitations with the slow rate of hydrate formation being one of the most prominent. The addition of surfactants like Sodium dodecyl sulfate (SDS) to the hydrate forming system significantly speeds up the process of methane hydrate formation but the large amount of foam generated by these surfactants during the process of hydrate formation and dissociation stands as a major roadblock towards the scaling up of the technology. In the current work, a small amount of a silicon based surfactant has been proposed to be used as antifoam in conjunction with an anionic surfactant SDS to eliminate the foam generation while at the same time promote the kinetics of methane hydrate formation. The idea is simple, cost effective and can be a potential game-changer in the quest to develop a commercially scalable hydrate based methane storage technology. (C) 2017 Elsevier Ltd.
Keywords: Antifoam; Gas hydrate; kinetics; Methane storage; scale-up; Silicone surfactant

Molecular view of CO2 capture by polyethylenimine: role of structural and dynamical heterogeneity - Sharma, Pragati; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Langmuir, 2018)
The molecular thermodynamics and kinetics of CO2 sorption in Polyethylenimine (PEI) melt have been investigated systematically using GCMC and MD simulations. We elucidate presence of significant structural and dynamic heterogeneity associated with the overall absorption process. CO2 adsorption in a PEI membrane shows a distinct two-stage process of a rapid CO2 adsorption at the interfaces (hundreds of picoseconds) followed by a significantly slower diffusion limited release toward the interior bulk regions of PEI melt (hundreds of nanoseconds to microseconds). The spatial heterogeneity of local structural features of the PEI chains lead to significantly heterogeneous absorption characterized by clustering and trapping of CO2 molecules that then lead to subdiffusive motion of CO2. In the complex interplay of interaction and entropy, the latter emerges out to be the major determining factor with significantly higher solubility of CO2 near the interfaces despite having lower density of binding amine groups. Regions having higher free-volume (entropically favorable) viz. interfaces, pores and loops demonstrate higher CO2 capture ability. Various local structural features of PEI conformations, for example, inter- and intrachain loops, pores of different radii, and di- or tricoordinated pores are explored for their effects on the varying CO2 adsorption abilities.

Comparison of different water models for melting point calculation of methane hydrate using molecular dynamics simulations - Choudhary, Nilesh; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Chemical Physics, 2019)
Molecular dynamics simulation is a powerful tool to understand the gas hydrate nucleation, growth, and dissociation at molecular level. Prerequisite of super-cooling during gas hydrate formation and a certain degree of super-healing during melting shows significant hysteresis in the transition between solid and liquid state due to large nucleation barrier. Different water models quantitatively differ in their prediction of thermodynamic and kinetic properties of bulk water, including phase behaviour. The present work carries out a systematic investigation of the effect of the chosen water model on the phase behaviour, in particular, the decomposition of methane hydrate. Void-induced melting has been used to predict the melting point of methane hydrate using TIP4P/Ice, TIP4P/2005, TIP4P, and SPC/E water models. This method avoids the need for a predetermined interface for melting point calculations and thus may have its importance in identifying dissociation kinetics of bulk hydrate.
Keywords: decomposition; Gas hydrates; Void-induced melting; Water models

Methane recovery from marine gas hydrates: a bench scale study in presence of low dosage benign additives - Bhattacharjee, Gaurav; Choudhary, Nilesh; Barmecha, Vivek; Kushwaha, Omkar S.; Pande, Nawal K.; Chugh, Parivesh; Roy, Sudip; Kumar, Rajnish (Applied Energy, 2019)
De-pressurization is one approach which has been found to be economically feasible for methane recovery from marine hydrates. Hydrate dissociation being an endothermic process suggests that de-pressurization alone would not be sufficient and some additional stimulation would be required for sustained production from one such reservoir. Thermal stimulation may overcome the challenge posed by the endothermic dissociation process; however, economically it may not be ideal. A possible way out is to use thermal stimulation, but at relatively low temperatures as compared to conventional practice. This would be economical and can be accomplished in the presence of small doses of additives mixed in with the water stream used for thermal stimulation. In the present study, a number of benign additives were identified which when used in low concentrations enhance the kinetics of methane hydrate dissociation compared to pure water. Additives were first shortlisted from a wide potential pool using quantum mechanical calculations. These additives were later tested for their efficacy in stirred tank reactor to quickly identify the best additives for the job and few selected additives were then studied in a larger bench scale setup (fixed bed configuration) where they were injected in the form of an additive-water stream to dissociate already formed hydrates. Factors such as toxicity of the additive, fluidity of additive-water stream, foam formation on mixing of additive with water, etc. were also taken into account. An energy and efficiency analysis revealed that reported additives enhance the energy ratio and thermal efficiency of the process as compared to pure water stimulation.
Keywords: Bench scale; kinetics; Marine hydrate; methane hydrate; Methane recovery; Natural gas hydrate; Process

Molecular dynamics study on growth of carbon dioxide and methane hydrate from a seed crystal - Nakate, Prajakta; Ghosh, Bappa; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Chinese Journal of Chemical Engineering, 2019)
In the current work, molecular dynamics simulation is employed to understand the intrinsic growth of carbon dioxide and methane hydrate starting from a seed crystal of methane and carbon dioxide respectively. This comparison was carried out because it has relevance to the recovery of methane gas from natural gas hydrate reservoirs by simultaneously sequestering a greenhouse gas like CO2. The seed crystal of carbon dioxide and methane hydrate was allowed to grow from a super-saturated mixture of carbon dioxide or methane molecules in water respectively. Two different concentrations (1:6 and 1:8.5) of CO2/CH4 molecules per water molecule were chosen based on gas-water composition in hydrate phase. The molecular level growth as a function of time was investigated by all atomistic molecular dynamics simulation under suitable temperature and pressure range which was well above the hydrate stability zone to ensure significantly faster growth kinetics. The concentration of CO2 molecules in water played a significant role in growth kinetics, and it was observed that maximizing the CO2 concentration in the aqueous phase may not result in faster growth of CO2 hydrate. On the contrary, methane hydrate growth was independent of methane molecule concentration in the aqueous phase. We have validated our results by performing experimental work on carbon dioxide hydrate where it was seen that under conditions appropriate for liquid CO2, the growth for carbon dioxide hydrate was very slow in the beginning. (C) 2019 The Chemical Industry and Engineering Society of China, and Chemical Industry Press Co., Ltd. All rights reserved.
Keywords: Cage dynamics; CH4 recovery; CO2 sequestration; F-4 order parameter; kinetics; Natural gas hydrate; Thermodynamics

Macro and molecular level insights on gas hydrate growth in the presence of hofmeister salts - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2020)
The effect of few monovalent salts (NaCl, NH4Cl, and GdmCl) as additives, according to the Hofrneister series on the growth of methane gas hydrates, has been studied using experiments as well as molecular dynamics (MD) simulation. Further, the Hofmeister effects on hydrate crystallization have been correlated with the methanol as an additive, which is a known thermodynamic hydrate inhibitor for hydrate growth. One of the previous studies (discussed later in this article) available in the literature concludes that methane hydrate formation from ice might show enhanced kinetics in the presence of salts; this behavior is contrary to the general usage of such salts as hydrate inhibitors. This conclusion may not necessarily be true for experiments done with liquid water, and therefore, this work explores the behavior of these salts in a lab-scale setup. In addition, current work reports detailed MD simulation studies to gain insight into the mechanism of hydrate formation in the presence of Hofmeister series salts at two different concentrations of 1 and 10 wt % in water and compare the results with hydrate formation in the methanol-water system. Our study suggests that the presence of these additives at low concentrations (1 wt %) does enhance the hydrate growth kinetics. However, at higher concentrations (10 wt %), inhibition by these additives persisted, and prolonged nucleation, as well as retarded growth, was observed.

Morphology and dynamics of self-assembled structures in mixed surfactant systems (SDS plus CAPB) in the context of methane hydrate growth - Hande, Vrushali; Choudhary, Nilesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Molecular Liquids, 2020)
Presence of small dosages of surfactants in the aqueous phase has been reported to enhance the rate of gas hydrate (clathrate) formation. In this work, using extensive atomistic molecular dynamics (MD) simulations, we have investigated how SDS (surfactant) aggregates in the presence/absence of CAPB (co-surfactant) at ambient conditions (temperature 298 K and pressure 1 bar) and at hydrate forming conditions (temperature 275 K and pressure 50 bar) resulting in altered growth kinetics of methane hydrate. We observe that SDS forms aggregates of different sizes and shapes depending on the thermodynamic condition starting from random distributions of the surfactants. In the presence of the CAPB co-surfactant, tightly packed mixed aggregates are formed. Using various structural order parameters, we demonstrate that shape of the aggregates deviates from spherical as well as cylindrical symmetry. During the aggregation process in presence of methane, the methane molecules get absorbed into the aggregates, enhance the aggregation kinetics and provide structural flexibility to the aggregates. This result is partly in agreement with previous experimental observations that SDS (with or without a co-surfactant) may form micelle-like structures under hydrate forming conditions and that methane gets absorbed by these aggregates leading to enhanced solubility of methane in the aqueous phase. Further, we have investigated the dynamics of shape fluctuations of the aggregates and observed that several distinct relaxation timescales exist in these heterogenous systems. (C) 2020 Elsevier B.V. All rights reserved.

Rhamonolipids produced by Pseudomonas aeruginosa promotes methane hydrates formation in fixed bed silica gel medium - Arora, Amit; Cameotra, Swaranjit Singh; Balomajumder, Chandrajit; Kumar, Rajnish; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Marine Geophysical Research, 2021)
Natural gas hydrates are seen as an alternative future energy source. They have also been valued for their carbon dioxide capturing capability, gas separation, desalination, natural gas storage and transportation. Developing economical and viable gas hydrate based technology is one of the most promising research areas of present decade. Successful commercialization of gas hydrate based technology is often curtailed due to slow formation rate. The present study evaluates biosurfactant as a kinetic promoter of methane hydrates formation in a fixed bed C type silica gel medium. Biosurfactant was produced by growing Pseudomonas aeruginosa strain A11 in glycerol supplemented mineral salt medium. Biosurfactant characterization with FTIR, NMR and MALDI-TOF spectroscopy reveled it to be a glycolipids type biosurfactant namely rhamnolipids. Saturating C type silica gel with of 100 ppm rhamnolipids solution enhanced the rate of methane hydrates formation by reducing the induction time. Mole of methane consumed and percentage of water to hydrate conversion was observed to be more in 1000 ppm rhamnolipids saturated C type silica gel as compared to quiescent water system and water saturated silica gel system. Overall results suggest that rhamonolipids produced by strain A11 in combination with silica gel can be utilized as environmentally safe kinetic promoter for methane hydrate formation.
Keywords: Biosurfactant; Energy; Glycolipids; Induction time; Kinetic promoter